(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
The information about new lichen species for the plain part of Ukraine – Lecanora strobilina (Spreng.) Kieff. is presented. It was found in artificial silvicultural forests in the valley of the Ingulets river on dry twigs of Pinus sylvestris L. Our sample is a second finding of Lecanora strobilina in Ukraine.